2009
DOI: 10.1260/136943309790327707
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Solution for Fatigue Debonding Growth and Fatigue Life Prediction of FRP-Concrete Interfaces

Abstract: This paper presents an analytical solution for the evolution and distribution of shear stresses along the entire bond length of FRP-concrete interfaces due to mode-II fatigue loading. The creep-fatigue interaction and fatigue crack growth after debonding initiation are incorporated into a nonlinear interfacial constitutive law. While the creep-fatigue interaction is represented by the degradation of the interfacial stiffness, the debond growth is governed by a form of the Paris equation and the fracture energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 15 publications
3
37
0
Order By: Relevance
“…Yun et al (2008) showed that the post-fatigue bond strength under monotonic static load was not influenced by the fatigue damages if a sufficient intact bond length was still available. Similar observations were also reported by Ko and Sato (2007), Diab et al (2009) and Mazzotti and Savoia (2009). However, after high-level fatigue loading, the FRP-concrete has a significant reduction in the bond stiffness under monotonic loads (Yun et al 2008).…”
Section: Post-fatigue Behavioursupporting
confidence: 87%
See 4 more Smart Citations
“…Yun et al (2008) showed that the post-fatigue bond strength under monotonic static load was not influenced by the fatigue damages if a sufficient intact bond length was still available. Similar observations were also reported by Ko and Sato (2007), Diab et al (2009) and Mazzotti and Savoia (2009). However, after high-level fatigue loading, the FRP-concrete has a significant reduction in the bond stiffness under monotonic loads (Yun et al 2008).…”
Section: Post-fatigue Behavioursupporting
confidence: 87%
“…For the bending test, FRP rupture usually occurs near the transverse crack where high stress concentration is present (Xie et al 2015). FRP debonding is the most common failure mode for the FRP-concrete interface under cyclic loading (Bizindavyi et al 2003, Ko and Sato 2007, Yun et al 2008, Diab et al 2009, Mazzotti and Savoia 2009, Nigro et al 2011, Carloni et al 2012, Carloni and Subramaniam 2013, Xie et at. 2015.…”
Section: Failure Modementioning
confidence: 99%
See 3 more Smart Citations